Mitochondrial membrane models built from native lipid extracts: Interfacial and transport properties - Schiaffarino, Olivia; Valdivieso González, David; García-Pérez, Inés M.; Peñalva, Daniel A.; Almendro-Vedia, Víctor G.; Natale, Paolo; López-Montero, Iván (Frontiers in Molecular Biosciences, 2022)
The mitochondrion is an essential organelle enclosed by two membranes whose functionalities depend on their very specific protein and lipid compositions. Proteins from the outer mitochondrial membrane (OMM) are specialized in mitochondrial dynamics and mitophagy, whereas proteins of the inner mitochondrial membrane (IMM) have dedicated functions in cellular respiration and apoptosis. As for lipids, the OMM is enriched in glycerophosphatidyl choline but cardiolipin is exclusively found within the IMM. Though the lipid topology and distribution of the OMM and IMM are known since more than four decades, little is known about the interfacial and dynamic properties of the IMM and OMM lipid extracts. Here we build monolayers, supported bilayers and giant unilamellar vesicles (GUVs) of native OMM and IMM lipids extracts from porcine heart. Additionally, we perform a comparative analysis on the interfacial, phase immiscibility and mechanical properties of both types of extract. Our results show that IMM lipids form more expanded and softer membranes than OMM lipids, allowing a better understanding of the physicochemical and biophysical properties of mitochondrial membranes.